J0S3PHK
J0S3PHK
18-03-2016
Mathematics
contestada
substitute y-x+6 x-2y=-6
Respuesta :
daniellionyang
daniellionyang
18-03-2016
I'm assuming equation 1 is y=x+6. x-2(x+6)=-6=>x-2x-12=-6=>-x=6=>x=-6. Solving for y, y=-6+6=0. (-6,0) is the answer.
Answer Link
VER TODAS LAS RESPUESTAS ( 44+ )
Otras preguntas
Why would hawaii have a military significancce for th united states
fair spinner a has four equal action labels 1,2,3,4
Solve the following exponential equation. Express the solution set in terms of natural logarithms or common logarithms. Then, use a calculator to obtain a dec
What is the difference between underextension and overextension?
Please help. All of my points.
Descubre how father de mora used slaves to mine the gold
fair spinner a has four equal action labels 1,2,3,4
atoms of elements that are in the same group have the same number of a-protons b-neutrons c-valence electrons d-protons and neutrons
solve first image second image am i correct other choices 1.fact 2.hypothesis 3.theroy dropdown 2 1.conduct electricy 2.generate hypothesis 3.hold different o
Convert the function into standard form: y = (x + 4)(x - 6) Show your work!!!
ACCESS MORE